A comprehensive capacity assessment tool for non-communicable diseases in low- to middle-income countries: development and results of pilot testing. (March 2018) - Garcia de Quevedo, Isabel; Lobelo, Felipe; Cadena, Loren; Soares, Madalena; Pratt, Michael
Non-communicable diseases (NCDs) are the leading causes of death worldwide, with higher rates of premature mortality in low- and middle-income countries (LMICs). This places a high economic burden on these countries, which usually have limited capacity to address this public health problem. We developed a guided self-assessment tool for describing national capacity for NCD prevention and control. The purpose of this tool was to assist countries in identifying key opportunities and gaps in NCD capacity. It was piloted in three countries between 2012 and 2013: Mozambique, Colombia, and the Dominican Republic. The tool includes details about NCD burden; health system infrastructure and primary care services; workforce capacity; surveillance; planning, policy, and program management; and partnerships. In the three pilot countries, the tool helped to identify differences in capacity needs pertaining to staff, training, and surveillance, but similarities were also found related to NCD challenges and opportunities. The NCD tool increased our understanding of needs and critical capacity elements for addressing NCDs in the three pilot countries. This tool can be used by other LMICs to map their efforts toward addressing NCD goals and defining priorities.